Taking the Two-Elements Theory of International Customary Law Seriously – Problems with Double Counting - Stępień, Michał (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
Among the few other preconditions of customary law F. Savigny mentions the “undertaking of the act in the feeling of a legal necessity (opinio necessitatis)” . As K. Wolfke explained, the two-element theory of customary law (according to which there are two constituent elements, i.e. practice and opinio iuris) was introduced to the modern theory of law by the historical school of law. The purpose of this concept was a departure from well-established understanding of the customary law as a tacit consensus populi. According to the generally agreed approach, international customary law is composed of an objective element, i.e. practice and the subjective element – so-called “opinio iuris”. This last one is usually understood as a feeling of doing one’s duty or simply doing what is right. Practice without opinio iuris is simply a “usage”. Alternatively, it can be a kind of international courtesy or protocol, which are loosely relevant for international law. The ICJ in the judgment in the case of North See Continental Shelf considered the premise of opinio iuris “the most important of all”. It is the differentia specifica of the customary law. Opinio iuris resembles tacit consent at least in one: both are opposite to usage.
Keywords: teoria prawa zwyczajowego; praktyka państwowa; opinie iuris